Pengelolaan Objek Wisata Situs Cagar Budaya Bukit Kerang Kelurahan Kawal oleh Dinas Kebudayaan dan Pariwisata Kabupaten Bintan - Ambar Rinah, Sri; Dewi Wulandari, Fitri; Fitriyani, Risky; Choiroel, Didyk (Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
In Bintan Regency, part of the Riau Islands, there is one tourist object of prehistoric cultural heritage, namely Shell Hill. It is known, the condition of the Bukit Kerang site is still poorly maintained, both in terms of the environment and infrastructure that have not been managed. With conditions that are not optimal, it will have an impact on the cultural heritage and regional income of Bintan. The purpose of this study is to see the management of the Dinas Kebudayaan dan Pariwisata which is carried out based on the Strategic Plan starting from the planning, organizing, implementing and supervising stages. The research method used is qualitative research with a descriptive approach, with observation, interviews and documentation. The results of this study indicate that in the management of Disbudpar the planning stage is only in the form of maintenance, the organizing stage of management is well structured, the implementation stage of management still lacks coordination between the Head of Disbudpar and the manager, so that supervision does not lead to evaluation from the Head of Disbudpar which has an impact on the development of reserve tourist attractions culture of Shell Hill Bintan Regency.